2001
DOI: 10.1136/sti.77.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Endocervical Gram stain smears and their usefulness in the diagnosis of Chlamydia trachomatis

Abstract: Objective: To evaluate the usefulness of endocervical Gram stain smears in the diagnosis of Chlamydia trachomatis and Neisseria gonorrhoeae in a female population attending a STD clinic. Methods: 494 females attending a STD clinic and undergoing a speculum examination had endocervical specimens submitted for C trachomatis culture, direct fluorescent antibody testing (DFA), and N gonorrhoeae culture. Endocervical smears were also collected for Gram stain. The number of polymorphonuclear leucocytes (PMN) per hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…79 Urine culture would have allowed us to establish the etiology of AB/UTI. Nucleic acid amplification tests would have allowed us to confirm if intracellular diplococci were Neisseria gonorrhoeae and to determine if Chlamydia was prevalent in this population (suspected based on our clinical findings, morphology of epithelial cells, and the presence of abundant leukocytes in the gram-stained vaginal smears 80 ). Our findings have several implications for clinical care of this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…79 Urine culture would have allowed us to establish the etiology of AB/UTI. Nucleic acid amplification tests would have allowed us to confirm if intracellular diplococci were Neisseria gonorrhoeae and to determine if Chlamydia was prevalent in this population (suspected based on our clinical findings, morphology of epithelial cells, and the presence of abundant leukocytes in the gram-stained vaginal smears 80 ). Our findings have several implications for clinical care of this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…Other subtle signs includes cervical ectopy with identification of ≥10 PMNLs per high power field in gram stained smear of cervical secretions [5,6]. The presence of above finding suggest either Neisseria gonorrhoea or Chalamydial infection but studies revealed that above organism are identified in only half or less than half of cases of cervicitis and causes of rest cases remain unknown [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, chlamydial antigen positivity was higher among women over 30 years of age compared to women under 30 years of age. In previous studies, C. trachomatis prevalence was found to be 2.5%-30.3% in vaginal discharge by various diagnostic techniques [3,16,19,21]. In Turkey, frequency of chlamydial infections in women is low, between 5.1% and 24% [20,22,23] for symptomatic patients and 1.11% [22] for asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Chlamydia trachomatis infections have been associated with increased rates of transmission of HIV [9]. Occasionally, the infection spreads to the upper genital tract in women, causing pelvic inflammatory disease, ectopic pregnancy, infertility, or to the epididymis in men, causing epididymitis [5,7,[9][10][11][12][13][14][15][16]. Bacterial vaginosis is believed to be the most common vaginal disorder affecting women and is characterized by the overgrowth of several anaerobic and microaerophilic bacteria and the decreased prevalence of Lactobacillus species due to alteration of the vaginal bacterial morphotypes [5].…”
Section: Introductionmentioning
confidence: 99%